Perancangan Interior Lego Day Care Centre di Surabaya - Fransiscus Alvian Tanjaya; mariana wibowo (Intra, 2014)
With the increased economies of many working parents. As a result of normal family life becomes hampered, especially the attention to children - children that they need a day care. Day care centers are child care facilities are divided into groups that are usually performed during working hours. Facilities provided are a play area, study area, sleeping area, a library, cafeteria, office manager laundry, and soon. Concepts used in the interior design of Lego Day Care Centre in Surabaya is